Standard management and prophylaxis - Rieke, Klaus; Ulatowski, John A.; Hacke, Werner (Neurocritical care, 1994)
This chapter reviews standard management protocols for patients with acute neurological diseases and may serve as a brief summary for physicians in the emergency department or in the neurocritical care unit. Most of the topics described are discussed in detail in other chapters.
Gesehen am 03.06.2025